Possible molecular mechanism for acute encephalopathy by angel-wing mushroom ingestion – Involvement of three constituents in onset –. (1st January 2023) - Suzuki, Tomohiro; Asakawa, Tomohiro; Maekawa, Fumihiko; Kimura, Eiki; Tezuka, Yuki; Nakamura, Luna; Sato, Takumi; Arai, Yuto; Choi, Jae-Hoon; Suzuki, Masakazu; Dohra, Hideo; Hirai, Hirofumi; et al.
Abstract: In Japan in 2004, 59 people who had consumed angel-wing mushroom, Pleurocybella porrigens, experienced acute encephalopathy, and of these 17 died. We purified a lethal protein to mice, pleurocybelline (PC), from P. porrigens . Although PC caused no damage to the brain, PC formed a complex with a lectin (PPL) and showed exo-protease activity, degrading substrates from both N - and C -termini. In addition, the presence of an unstable toxic compound, pleurocybellaziridine (PA), in the mushroom was demonstrated. We hypothesized that the complex and PA are involved in disease development and verified that apoptotic cells in the hippocampus were significantly increased by injection of the mixture of PC, PPL, and PA, indicating that these substances might be involved in acute encephalopathy. Graphical abstract: Image 1 Highlights: ・In Japan, 17 people who ate Pleurocybella porrigens died due to acute encephalopathy. ・A lethal protein, pleurocybelline (PC) was purified from the mushroom. ・The complex of PC and the lectin (PPL) from the fungus showed exo-protease activity. ・A low molecular toxin, pleurocybellaziridine (PA), from the fungus has been reported. ・Abnormity in the brains in mice was observed only by the mixture of PC, PPL and PA.